A Brief History of Schizosaccharomyces pombe Research: A Perspective Over the Past 70 Years. Issue 2 (1st June 2016) - Fantes, Peter A; Hoffman, Charles S
Abstract: Since its humble start as a model organism in two European laboratories in the 1940s and 1950s, the fission yeast Schizosaccharomyces pombe has grown to become one of the best-studied eukaryotes today. This article outlines the way in which interest in S. pombe developed and spread from Europe to Japan, North America, and elsewhere from its beginnings up to the first International Meeting devoted to this yeast in 1999. We describe the expansion of S. pombe research during this period with an emphasis on many of the individual researchers involved and their interactions that resulted in the development of today's vibrant community.